Performance of selected funds in the perspective of ESG constraints - Aaron, Ira; Zezula, Jakub; de Batz de Trenquelléon, Laure Sabine Marie; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines the impact of ESG integration on private equity performance through a comparative case study of two major firms: Apollo Global Management and KKR. Using fund-level performance data and matched fund pairs, the analysis finds no consistent evidence that ESG constraints significantly enhance or reduce returns. Statistical testing confirms that most differences are marginal and not significant. The findings suggest that ESG integration, as currently practiced, functions more as a reputational or compliance feature than a source of financial outperformance. The thesis also highlights structural challenges, such as inconsistent ESG definitions, limited transparency. Recommendations include improving ESG reporting standards, designing region-sensitive policy, and encouraging further research into ESG’s long-term and portfolio company-level effects.
Vedoucí práce: Jakub Zezula
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses